How to find love in a bookshop - Henry, Veronica (New York : Viking, 2017)
"The enchanting story of a book shop, its grieving owner, a supportive literary community, and the extraordinary power of books to heal the heart. Nightingale Books, nestled on the main street in an idyllic little village, is a dream come true for book lovers--a cozy haven and welcoming getaway for the literary-minded locals. But owner Emilia Nightingale is struggling to keep the shop open after her beloved father's death, and the temptation to sell is getting stronger. The property developers are circling, yet Emilia's loyal customers have become like family, and she can't imagine breaking the promise she made to her father to keep the store alive. There's Sarah, owner of the stately Peasebrook Manor, who has used the book shop as an escape in the past few years, but it now seems there's a very specific reason for all those frequent visits. Next is roguish Jackson, who, after making a complete mess of his marriage, now looks to Emilia for advice on books for the son he misses so much. And the forever shy Thomasina, who runs a pop-up restaurant for two in her tiny cottage--she has a crush on a man she met in the cookbook section, but can hardly dream of working up the courage to admit her true feelings"--
"Pamela Dorman Books."
Keywords: FICTION / Contemporary Women; FICTION / Family Life; FICTION / Cultural Heritage